POU2F1 activity regulates HOXD10 and HOXD11 promoting a proliferative and invasive phenotype in head and neck cancer - Sharpe, Daniel J.; Orr, Katy S.; Moran, Michael; White, Sharon J.; McQuaid, Stephen; Lappin, Terence R.; Thompson, Alexander; James, Jacqueline A. (Impact Journals, 2014)
HOX genes are master regulators of organ morphogenesis and cell differentiation during embryonic development, and continue to be expressed throughout post-natal life. To test the hypothesis that HOX genes are dysregulated in head and neck squamous cell carcinoma (HNSCC) we defined their expression profile, and investigated the function, transcriptional regulation and clinical relevance of a subset of highly expressed HOXD genes.